Antipsychotic Drugs Alter Functional Connectivity between the Medial Frontal Cortex, Hippocampus, and Nucleus Accumbens as Measured by H215O PET - Bolding, Mark S.; White, David M.; Hadley, Jennifer A.; Weiler, Martin; Holcomb, Henry H.; Lahti, Adrienne C. (Frontiers in Psychiatry, 2012)
To evaluate changes in functional connectivity as a result of treatment with antipsychotic drugs (APDs) in subjects with schizophrenia (SZ), we identified a limited number of regions that have been implicated in the mechanism of action of APDs and that are part of a neuronal network known to be modulated by dopamine (DA). These regions consisted of the nucleus accumbens (NAcc), the hippocampus (Hip), and the medial frontal cortex (MFC). SZ participants were blindly randomized into a haloperidol treatment group (n = 12) and an olanzapine treatment group (n = 17). Using PET with 15O, we evaluated changes in functional connectivity between these regions during rest and task performance at three treatment time points: (1) at baseline, after withdrawal of all psychotropic medication (two weeks), (2) after one week on medication, and (3) after 6 weeks on medication. Results from the two treatment groups were combined during analysis to investigate the common effects of APDs on functional connectivity. We found that the functional connectivity between MFC and NAcc significantly increased at week one, and then significantly decreased from week one to week 6. The functional connectivity between MFC and Hip significantly decreased at week one and week 6 relative to baseline. Critically, the strength of the functional connectivity between the MFC and Hip after one week of treatment was predictive of treatment response. This pattern of changes may represent an important biomarker for indexing treatment response. The regulation by APDs of the balance between prefrontal and limbic inputs to the striatum may be crucial to restoring adaptive behavior.